THE CONCEPT OF RASA IN PHILOSOPHY OF K. C. BHATTACHARYA - Корниенко, Людмила; Корниенко, Александр (SWorldJournal, 2022)
The article deals with the aesthetic views of the famous Indian philosopher of the colonial period K.S. Bhattacharya, namely his interpretation of the theory of Rasa. The author, through the analysis of the texts of Bhattacharya's philosophical works "Su